Aspectos imunopatológicos da infecção por Schistosoma mansoni em pacientes com baixa carga parasitária e com histórico de Leishmaniose Tegumentar Americana - Guilherme Silva Miranda (2018)
Helminths such as Schistosoma mansoni and protozoa of the genus Leishmania are parasites with high prevalence in the human population and responsible for high rates of mortality and worldwide morbidity. Due to the wide distribution of the transmission areas of these parasitoses, especially in tropical and subtropical areas of the globe, the risk of concomitant infection is frequent. However, the impact that this type of interaction can cause infectious in patients living in endemic areas is still poorly elucidated. Thus, we aimed to characterize the parasitological, immunological, hematological, clinical and ultrasonographic aspects of patients infected with S. mansoni with low parasite load and with a history of infection by American cutaneous leishmaniasis (ACL). For this, 257 residents of Brejo do Amparo district (MG) signed a term of consent to participate in the study and were asked to respond socioeconomic questionnaire and provide stool and blood samples. Stool samples were processed to perform HPJ, Gradiente Salino, Helmintex® and Kato-Katz techniques and analyzed for parasitological diagnosis. Blood samples were used to perform the hemogram (platelets, hemoglobin, red blood cells and eosinophils) and to obtain serum for quantification of total IgE levels and cytokines and chemokines. Individuals with positive parasitological examination for S. mansoni were invited for clinical and ultrasonographic examination of the abdomen and the data were used to establish the degree of schistosomiasis morbidity for each infected patient. The identification of ACL history was obtained through individual socioeconomic and clinical records, as well as the use of medical records from the Leishmaniasis Treatment and Research Center from Januária municipality (2006-2015). The data revealed that the study population lives in precarious sanitary conditions, has low schooling and income, which favors the transmission of parasitoses. Parasitological tests demonstrated that S. mansoni infection was the most prevalent parasite in the population (n=119; 46.30%), and 91.6% of infected individuals eliminated less than 100 eggs/g. feces, which characterizes as a population with low parasitic load, and without severe symptoms of the disease. In this population, 93 individuals (36.18%) have reported ACL, and the prevalence of schistosomiasis in these individuals was significantly higher than in the nonreporting group (p=0.039). However, when considering only those infected with a slightly higher parasite load (12 eggs / g feces), it is verified that people with a history of ACL eliminate fewer eggs from the parasite in feces. Most of the individuals evaluated did not present measurable serum levels of the cytokines IL-17, TNF-, IL-10, IL-13 and IL-5, regardless of parasitic status. Patients infected with S. mansoni had statistically higher concentrations of CCL-3 and higher frequency of individuals with eosinophilia compared to individuals with a history of ACL, indicating a predominantly Th2-profile immune response. In this sense, serum levels of IL-33, CCL-17 and IgE, and IL-27 reduction were also observed, but there was no statistically significant difference between groups. Individuals infected with S. mansoni and with a history of LTA also showed elevation of these immunological mediators, but generally at lower levels than those only infected by S. mansoni. Although individuals with schistosomiasis evaluated in this study showed few clinical signs, it was possible to verify that individuals only infected with S. mansoni presented a higher frequency of low hemogloblin and platelet count compared to those infected with a history of ACL. Most ultrasonographic changes observed in patients infected with S. mansoni and without a history of ACL were similar to those seen in patients with history. In summary, the data presented suggest that the history of ACL can alter the balance of cytokines produced during S. mansoni infection, modifying the production and/or elimination of eggs of the parasite and, consequently, the severity of schistosomiasis